Tobacco-related risk behaviors among amateur rugby players, coaches and referees: targets for prevention. (14th October 2021) - Chague, F; Israel, J; Guinoiseau, J P; Garet, G; Reboursiere, E; Ngassa, P; Hager, J P; Geneste, M; Sarda, J; Dincher, J C; Cottin, Y; Zeller, M
Abstract: Background: High prevalence of smoking has been documented in France and new patterns of tobacco and nicotine consumption are emerging, especially in some sports. In amateur rugby population, such attitudes could be harmful, but data are scarce as well as their knowledge of the risk. Purpose: We analyzed tobacco consumption in French amateur players, coaches and referees. Methods: Each amateur players [>12-y/o], coaches and referees licensed in the French Rugby Federation and participating in the Burgundy amateur championship was invited to answer to an electronic anonymous questionnaire during the 2017–2018 sport season. Results: 683 [sex ratio M/F = 0.9] answers were obtained and fit for analysis. Among them, 559 (81.8%) were players, 167 (24, 5%) were coaches and 74 (10.8%) were referees. 176 subjects (25.8%) were current smokers, 126 (18.4%) daily smokers, 54 (37% of usual smokers) smoked more than 10 cigarettes a day and 97 (14.2%) were ex-smokers. Moreover, 24 referees (32.4%) and 47 coaches (28.2%) were current smokers. Most smoked 2 hours before or after a rugby session (86.4% of smokers), including coaches (89.4%) and referees (89%). Although 109 smokers (61.9%) considered quitting, only 27 (24.8%) considered vaping to aid them. Only 28 subjects (4.1%) usually vaped, of whom 15 daily (1.9%); 21 of them (75%) vaped in the 2 hours before or after a rugby session. Number of cigarettes in the 19 dual users was not different compared with non-vaping smokers. Among the 28 vapers, motivation to vape included lower risk than smoking (13), consider to quit (12), cheaper than smoking (8), festive and socializing (6), avoid to smoke (3), respect the performance (2). Other tobacco or nicotine products were infrequent: waterpipe (7), dry snuff (1) and none used snus. The knowledge about risk was incomplete: 35 (5.1%) subjects do not know that smoking is dangerous for their health and 12 (1.8%) think it is not. 246 (36%) and 195 (28.6%) do not know if smoking is more dangerous in the 2 hours before or after sport; 45 (6.6%) and 18 (2.6%) think it is not. Moreover, 27.5% of coaches were unaware on the risk of smoking before a sport session and 19.2% on the risk after. 244 subjects (35.7%) do not know if vaping is less dangerous than smoking; 272 (39.8%) are not informed of the potential risk of nicotine when vaping. Conclusion: Despite information, prevalence of smoking remains high in the French amateur rugby players, coaches and referees. Smokers usually smoke in the 2 hours before or after the sport session. This is dangerous for them and for their peers. The low knowledge about the CV risk is of great concern, especially when considering the coaches and referees considering both their symbolic position and their educational role. Vaping and other patterns of nicotine exposure are infrequent; none of them use snus. Targeted education programs are urgently needed to reduce acute and chronic risk of tobacco consumption in this population. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): CHU Dijon Bourgogne ARS Bourgogne Franche Comté